O12.3 Epidemiological impact of expedited partner therapy for men who have sex with men: a modeling study. (14th July 2019) - Weiss, Kevin; Jones, Jeb; Katz, David; Gift, Thomas; Bernstein, Kyle; Workowski, Kimberly; Rosenberg, Eli; Jenness, Samuel
Abstract : Background: Expedited partner therapy (EPT) is an intervention for patients with gonorrhea (NG) or chlamydia (CT), through which index patients are provided with medication to give to their partner. While EPT is recommended for heterosexuals, EPT is not recommended for men who have sex with men (MSM), partially due to concerns about overtreatment of uninfected partners and missed opportunities for HIV diagnosis. In this study, we used modeling to investigate the potential impact of EPT implementation on STI incidence among MSM in the United States. Methods: We extended our stochastic network-based mathematical model of HIV, NG, and CT among MSM to include partner-delivered EPT for NG and CT. EPT implementation was simulated for 10 years. Counterfactual scenarios varied EPT coverage, provision, uptake, and partnership window duration. We estimated STI incidence, percent of infections averted (PIA), and process outcomes under each scenario, compared to a reference scenario that included routine and symptoms-based STI screening at current empirical levels among US MSM. Results: Delivery of EPT to 20% of eligible MSM index patients (coverage) was projected to reduce cumulative STI infections among MSM by 22% over 10 years compared to current estimated STI screening levels. A 20% increase in providing medication to non-index partners (provision) averted 29% of STI infections compared to STI screening. By partnership type, intervention benefits were greatest when EPT was restricted to casual partners. The proportion of partners given medication who had no current STI varied from 55% to 65%, depending on coverage. The proportion of partners given medication with undiagnosed HIV infection was 4%. Conclusion: EPT could substantially reduce bacterial STI incidence for MSM. However, this intervention could result in a substantial increase in unnecessary use of antibiotic medication by STI-uninfected MSM, raising concerns about cost and antimicrobial resistance in absence of additional medical evaluation. Disclosure: No significant relationships.